1995
DOI: 10.1577/1548-8659(1995)124<0194:bibcsa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interaction between Chinook Salmon and Brown Trout Juveniles in a Simulated Stream

Abstract: The behavioral interaction between underyearling chinook salmon Oncorhynchus tshawytscha and brown trout Salmo trutta, both exotics in an unnatural sympatry in New Zealand, was tested during spring and summer in a simulated stream containing natural food. Both species were highly territorial and actively defended preferred drift-feeding sites and resting areas in the pool. Species dominance differed with season and was influenced by prior residence. In spring, chinook salmon were larger (because of their earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
(32 reference statements)
1
35
0
Order By: Relevance
“…Consequently, differences in the relative amounts of drifting and benthic invertebrates associated with riparian willows have important implications for both the composition and the quantity of potential prey available to trout. In a study of the behaviour of juvenile salmonids in a simulated stream, Glova & Field-Dodgson (1995) reported that during their summer experiment brown trout (50-100 mm FL) fed primarily on drifting organisms; prey were taken from near the bottom and in mid water (about 45% each of the number of observations), the benthos (10%), and at the surface (about 1%). If we assume Table 8 Prey selection indices as calculated from the numbers of invertebrates in each of the principal prey categories in the diets of juvenile Salmo trutta in relation to those found in the benthos and drift during the day in each of three streams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, differences in the relative amounts of drifting and benthic invertebrates associated with riparian willows have important implications for both the composition and the quantity of potential prey available to trout. In a study of the behaviour of juvenile salmonids in a simulated stream, Glova & Field-Dodgson (1995) reported that during their summer experiment brown trout (50-100 mm FL) fed primarily on drifting organisms; prey were taken from near the bottom and in mid water (about 45% each of the number of observations), the benthos (10%), and at the surface (about 1%). If we assume Table 8 Prey selection indices as calculated from the numbers of invertebrates in each of the principal prey categories in the diets of juvenile Salmo trutta in relation to those found in the benthos and drift during the day in each of three streams.…”
Section: Discussionmentioning
confidence: 99%
“…However, the density of terrestrial organisms in the drift is usually greater near the surface , where juvenile brown trout rarely feed (Glova & Field-Dodgson 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the first juvenile rainbow trout, O. mykiss (Walbaum) introduced to an artificial stream also established a permanent size gap compared with later introductions of trout (Chandler & Bjornn, 1988). Prior residence also affects interspecific interactions: a similar phenomenon was documented between Atlantic salmon and brown trout in the wild (Egglishaw & Shackley, 1973), between chinook salmon, O. tshawytscha (Walbaum) and brown trout (Glova & Field-Dodgson, 1995), and between coho salmon, brook trout, Salvelinus fontinalis (Mitchill), and brown trout (Fausch & White, 1986). However, these studies used longer time intervals between early and late fish, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Ersbak and Haase, 1983;Arias et al, 1995;Weiss and Schmutz, 1999) who also found lower post-stocking survival of artificially-reared fish. Competitive superiority of resident salmonids over introduced fish (Brännäs, 1995;Glova and Field-Dodgson, 1995), known as the 'prior residence effect' (Huntingford and DeLeaniz, 1997; Rhodes and Quinn, 1998), was a possible reason for lower recapture rate of artificially reared fish in comparison with the wild in the Within a column, different superscripts letters indicate a significant difference (P < 0.05). present study.…”
Section: Discussionmentioning
confidence: 99%